Indikation zur laparoskopischen Pankreasoperation: Ergebnisse einer Konsensuskonferenz und des bisherigen laparoskopischen Pankreasregisters - Siech, Marco; Werner, Jens (Der Chirurg, 2012)
Laparoscopic pancreatic surgery is not common practice in Germany and is only carried out in approximately 20 clinics but with an increasing trend. The reasons for this are manifold, such as the current selection of patients and both skills in laparoscopic and pancreatic surgery are necessary to perform this operation safely. In 2008 a registry called „Laparoscopic pancreatic surgery“ was implemented to collect enough data in Germany to find out whether the resection is safe, feasible and beneficial for the patient.For further development of new laparoscopic techniques new data is needed. A group of experts performing laparoscopic pancreatic surgery in Germany supplied their data for the German registry for laparoscopic pancreatic resection and a consensus conference about the indications became necessary. This consensus conference discussed in particular the indications for laparoscopic pancreatic resection. A consensus was found by all members of the conference utilizing currently available evidence-based data.It was suggested that all data of laparoscopic pancreatic surgery should be evaluated in the German Registry. A consensus was made which diseases were either suitable for laparoscopic resection or not suitable or suitable in selected cases.